Effect of myo-inositol and d-chiro-inositol on improving hormonal, metabolic and reproductive parameters in women with polycystic ovary syndrome: A review of studies - Ciuła, Aleksandra; Borawski, Michał; Jakubiak, Anna; Miśkiewicz, Joanna; Kuźnieców, Tadeusz; Karaban, Łukasz; Znamirowska, Patrycja; Mularczyk, Klaudia; Kupis, Magdalena; Paszkowska, Monika (Quality in Sport, 2025)
Polycystic ovary syndrome (PCOS) is a leading cause of anovulatory infertility, affecting 6–12% of women of reproductive age. It is characterized by hormonal and metabolic disturbances, including insulin resistance, hyperandrogenism, and dyslipidemia, which significantly impair reproductive function and overall health. Effective management of PCOS requires a multifactorial approach combining pharmacotherapy, dietary intervention, and physical activity. This literature review aims to evaluate the therapeutic potential of inositol, particularly myo-inositol (MI), in the treatment of PCOS, with a focus on its impact on metabolic, hormonal, and reproductive parameters. Scientific articles published within the last 10 years were selected from PubMed and Google Scholar using specific keywords related to inositol supplementation in PCOS. The analysis demonstrates that MI supplementation improves insulin sensitivity, lowers androgen levels, enhances follicular development, and improves oocyte quality. Furthermore, combination therapy with MI and metformin yields superior outcomes compared to monotherapy, including improved menstrual regularity, reduced hyperandrogenic symptoms, and increased conception rates. Evidence also suggests enhanced outcomes in assisted reproductive technologies, such as in vitro fertilization (IVF), following MI use. The combined application of MI, D-chiro-inositol, metformin, and lifestyle modifications appears to exert a synergistic effect, optimizing hormonal balance and fertility, while also mitigating long-term metabolic and cardiovascular risks in women with PCOS.